Turnover Intention and Employee Retention: Identifying Key Factors and Mitigation Strategies at PT. XYZ - Suci Meldiana; Anggara Wisesa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The high employee turnover rate poses a significant challenge for organizations, especially in industries that require experienced labor. PT. XYZ faces this issue, especially with employees under 30 years old. This impacts workforce stability and the achievement of long-term targets. This research aims to identify the key components that influence the desire to change jobs and to develop useful methods for improving employee retention in the company. This research was conducted qualitatively, using thematic analysis based on semi-structured interviews with employees, former employees, and the company's HR. The research results show that factors causing employee dissatisfaction, such as unclear career paths, heavy workloads, lack of appreciation, and the monotonous nature of the work, are the reasons for employee turnover intention. Additionally, the causes of employee turnover intention are cognitive disengagement due to lack of managerial support and lack of organizational commitment. Many workers see their jobs as stepping stones rather than choices for a long-term career. This research proposes that job redistribution is the best way to manage workload. To carry out this redistribution, a workload analysis must be conducted first. It is highly recommended to use the Subjective Workload Assessment Technique (SWAT) to evaluate the mental, psychological, and time aspects of the workload. This analysis can help reduce workplace stress and distribute tasks more effectively. Additionally, strategic delegation is considered important to enhance productivity and ensure that responsibilities are distributed more evenly among staff members, thereby creating a more balanced work environment. PT. XYZ can improve retention, create a supportive work environment, and ensure human resource sustainability by addressing this issue. These results provide a foundation that can be used to build successful retention strategies that can be applied in similar industries.